Use of potato processing by-product: Effects on the 3D printing characteristics of the yam and the texture of air-fried yam snacks. (May 2020) - Feng, Chunyan; Zhang, Min; Bhandari, Bhesh; Ye, Yufen
Abstract: 3D printing is a promising technology that has attracted widespread attention from academia. In this work, the mixed powder of yam and potato processing by-product (PP) were 3D printed at mass ratios of 10:0, 9:1, 8:2 and 7:3 with various infill levels (20%, 50%, and 80%) and printing structures (parallel-structures, cross-structures, and complex structures). All formulation showed good printing characteristics and printed products were closer to the model geometry. The mixed powder of yam and PP at a mass ratio of 7:3 showed a higher G'. Printing variables (infill levels and infill structures) affected the weight and porosity of printed products. Low infill level resulted in products with low weight and high porosity, and vice versa. The effect of the infill structures on the weight and porosity of the printed product was linked to the infill level. The printed products were then post-processed. Air-frying change the quality of the product. The degree of deformation of the product was affected by the amount of PP added and the direction of the printed lines. The hardness of air-fried products decreases with increasing porosity. Printing variables affected the physical characteristics of the printed product and the shape and hardness of the air-fried product. Highlights: 3D printed high-fiber yam snack can be developed by the use of potato by-product. Adding potato processing by-product can reduce the bending height of air fried product. Infill rates and pattern structures affect product hardness by affecting porosity. Material properties and printing path or line direction affect the bending height.